Evaluación Ambiental y Económica de la Disposición Final de Residuos sólidos urbanos municipales de Moyobamba – 2015 - Rojas Camacho, Xiomy Daniela (2016)
The present research work seeks to carry out an Environmental and Economic Assessment Mainly of 3 most important stages that the operative part of the management Municipality of solid waste in the city of Moyobamba, I am referring specifically to the Stages of collection, transportation and final disposal of solid waste; the latter Is the phase that causes major problems for both the economic part (activities Of operation and maintenance in the municipal dump) and pollution problems That causes ecosystems such as soil, water, air, flora, fauna and loss of value Of the property (surplus value). In addition, the present research presents an evaluation of the income versus The expenses of the provision of solid waste services provided by the Municipality Provincial of Moyobamba as well as a weighting of environmental impacts Negative effects of the poor technical and environmental management of the Final disposal of such waste (Open-pit Municipal Moyobamba - Yantaló road). This research identifies certain problems and critical points of the whole cycle Management of municipal solid waste, An analysis of the collection and / or contribution made monthly by the Users of the public cleaning service. Likewise, this final thesis report consolidates the weighting Evaluation of matrices of identification of incidents and / or negative environmental impacts Which causes the inadequate final disposal stage of solid waste; Which in this case Particular is "REGULAR IMPACT" (weighting 0.5).